Changes in alcohol use following the transition to motherhood: Findings from the National Epidemiologic Survey on Alcohol and Related Conditions. (1st November 2016) - Matusiewicz, Alexis K.; Ilgen, Mark A.; Bohnert, Kipling M.
Highlights: Examines changes in alcohol use among new mothers and non-mothers. Mothers showed reduced frequency of alcohol use and binge drinking. Non-mothers showed increased frequency of alcohol use and binge drinking. Differences remained after adjusting for demographic factors and baseline alcohol use. Abstract: Background: Little is known about the impact of motherhood on alcohol use beyond the acute reductions observed in pregnancy. This study characterizes changes in alcohol use for women who did and did not become mothers over three years. Methods: Data are from the National Epidemiologic Survey of Alcohol and Related Conditions (NESARC). Participants were female respondents aged 18–44 years who did not have children and were not pregnant at wave 1, and who reported having at least one drink in the year prior to wave 1 (n = 2118). Women were classified as mothers (n = 325) if they reported having a child between waves 1 and 2, and non-mothers if they did not (n = 1793). At each wave, participants provided information on past-year frequency of alcohol use and heavy episodic drinking, and usual number of alcoholic beverages consumed per occasion. Results: At baseline, women who did and did not become mothers reported similar levels of alcohol use. Women who became mothers reported significant reductions in alcohol use indicators from wave 1 to wave 2 (i.e., 22 fewer drinking days, 15 fewer heavy drinking days, 1 less drink per occasion), whereas women who did not become mothers showed a modest increase in alcohol use frequency (i.e., 7 more drinking days). Motherhood remained significantly associated with reductions in alcohol use after adjusting for sociodemographic variables and baseline alcohol use. Conclusions: The transition to motherhood is associated with marked reductions in alcohol consumption. Similar reductions were not observed for women who did not become mothers.